Tools for the Involvement of Construction and Demolition Waste in the Repeated Production Cycle - Shuvaev, A. A. (Science and Transport Progress, 2023)
Purpose. This paper aims to analyze and classify construction and demolition waste. It is necessary that this classification not only reflects statistical data on waste generation, but also serves as an information basis for the integrated waste management system (IWMS). The main task of this system is to maximize the involvement of waste in economic recycling and to objectively reflect the technological capabilities of its processing. This is extremely important in the context of the implementation of European waste management principles and the implementation of the National Waste Management Strategy in Ukraine until 2030. Methodology. The article considers the problems of construction waste management within the framework of the National Waste Management Strategy in Ukraine until 2030, which provides for the implementation of measures and principles of waste management, including construction waste. The author analyzes the management problems in the field of construction and demolition waste, which substantiates the need to classify construction waste with the simultaneous harmonization of processing methods and technologies. Construction activities are inextricably linked to the management of various types of resources, among which secondary materials play a key role in the implementation of construction processes. The ability to effectively manage the flows of these secondary resources is critical to ensuring the sustainability and efficiency of construction production. In this context, the study of the importance of managing the flows of secondary resources becomes an integral part of strategies for optimizing construction processes. Findings. Construction waste from the demolition of buildings and structures is unique due to its size and the need to prepare it for primary crushing. This is especially true in the context of implementing the concept of renovation of the outdated housing stock. Various static and dynamic methods of destruction of building materials, in particular, impact and vibration, have been investigated, with dynamic methods being characterized by lower energy consumption. Originality. The work reflects the formation of theoretical and methodological directions based on the use of recycled materials in construction, as well as a comparative characterization of various methods of destruction of building materials. Practical value. The possibilities of recycling construction waste, in particular, their maximum involvement in recycling, which meets the goals of the Strategy of Ukraine, provides 50% of waste recycling.